Linguistic categorization of teacher perceptions about BIPA learner errors and learning challenges: a multiple case study - Spenser Edward Lemaich; Sri Utami (Badan Pengembangan dan Pembinaan Bahasa, 2022)
This descriptive qualitative study investigated teacher perceptions about common BIPA learner errors and challenges, to contribute to the formation of a larger profile of Indonesian language learners and assist both materials developers and classroom teachers in anticipating and addressing these challenges. The data in this multiple case study was collected through interviews of four experienced BIPA instructors representing a range of instructor backgrounds with regard to gender, years taught, international teaching experience, and teaching context, although all were from a language, linguistics or humanities background. Learners taught ranged from approximately 15 national backgrounds, with the largest group being Australians, and most being in the A1-A2 CEFR range. Errors and challenges were identified in the areas of phonology, morphology, semantics, syntax, pragmatics, and with regard to language contact. The participants disagreed about the usefulness of existing BIPA materials, with some suggesting the need for more specialized materials.